KATEGORISASI DAN PERIODESASI SASTRA LISAN BIMA - Muhammad Alfian Tuflih; Mayong Mayong; Salam Salam (Universitas Negeri Makassar)
Abstract: Categorization and Periodization of Bima's Oral Literature. Thisstudy aims to: 1) examine the categories of oral literature found in the Bima tribe;and 2) examine the period of Bima's oral literature. This research is a qualitativeresearch using a qualitative descriptive research design. The subject of thisresearch is Bima Oral Literature. While the object of study is the categorization ofBima's oral literature. The data analysis model used in this study adopts aninteractive data analysis model which consists of four activity streams namelydata collection, data reduction, data presentation, and drawing conclusions. Theresults showed that the categorization of Bima's oral literature consisted ofrhymes, folk songs, and folk tales. While the periodization of Bima's oralliterature began since the time of the Bima kingdom.